PENINGKATAN PEMAHAMAN KONSEP IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) PADA KELAS IV SDS KHUSUS INSAN HARAPAN - Dwi Utami, Nanda; Yunus, Mahmud; Amir Soleh, Dudung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ understanding of social studies concepts through the implementation of the cooperative learning model Teams Games Tournament (TGT). The background of this research is the low level of students’ conceptual understanding in social studies learning. The subjects of this study were 32 fourth-grade students of SDS Khusus Insan Harapan. This research employed a Classroom Action Research design based on Kemmis and McTaggart, conducted in two cycles consisting of planning, action, observation, and reflection. The data were collected through tests, observation, and documentation. The results showed that students’ learning mastery improved from 63% in the first cycle to 84% in the second cycle, achieving the success indicator of at least 80% of students reaching the minimum mastery criteria. In addition, teacher performance increased from 91% to 100%, and students’ learning activities improved from 73% to 98%. These findings indicate that the implementation of the TGT model is effective in improving students’ conceptual understanding, learning activities, and the quality of the learning process in social studies.